Analisis Penerapan Model RME Berbasis Budaya dalam Pembelajaran Matematika: Systematic Literature Review - Kanaya Chintia Lauren Siahaan; I Made Sugiarta; Kadek Ayu Mutiara Pratiwi; I Made Suarsana (CV. Alim's Publishing, 2026)
This study aims to analyze in depth the effectiveness of Realistic Mathematics Education (RME) and ethnomathematics in improving students’ mathematical abilities through a Systematic Literature Review (SLR) approach. This study is motivated by the low level of students’ conceptual understanding, mathematical literacy, and mathematical communication skills, which are still dominated by conventional teaching approaches. Data were collected from ten research articles relevant to the topics of RME and ethnomathematics. The analyzed articles employed various research methods, including experimental research, classroom action research, and research and development (R&D). The results of the review indicate that the implementation of RME is consistently effective in enhancing students’ mathematical abilities, such as critical thinking, problem-solving, mathematical communication, and mathematical literacy. The RME approach, which is based on real-life contexts, helps students understand mathematical concepts more deeply and meaningfully. In addition, the integration of culture through ethnomathematics strengthens the effectiveness of learning by providing contexts that are closely related to students’ daily lives, thereby increasing motivation, engagement, and active participation in the learning process.Furthermore, the findings reveal that the success of culture-based RME is influenced by instructional design, the selection of appropriate contexts, and the teacher’s role in managing the learning process. Therefore, culture-based RME can be considered an effective and relevant approach to improving the quality of mathematics education.